The Expansion of Vending in the Automated Retail Sector: An Experiential Marketing Approach to Customer Acquisition - A Case Study of MatiPay Srl, Italy - Di Vittorio, Arianna; Di Gioia, Vito Alessandro (European Scientific Journal, ESJ, 2025)
“Automated retail” and “vending” refer to the sale of products through machines, often without direct human intervention, acting as unattended points of sale. This includes beverage vending machines, smart fridges, self-service laundromats, car washes, electric car charging stations, and more. Vending is a specific form of automated retail where the vending machine acts as an autonomous point of sale and a payment point. Simultaneously, it serves as a promotional and marketing tool for customer engagement. This objective is both comprehensive and complex, as the point of sale is entirely digital and unattended, yet it establishes a connection and digital dialogue with the customer through dedicated commercial offers and promotional messages. This process creates an innovative Customer Experience that links the customer to novel methods of communication and payment, thereby redefining the brand’s image and reputation. The primary aim of this paper is to demonstrate the importance of implementing automated payment and telemetry systems to facilitate product sales and service delivery, enabling businesses to reach customers anywhere, even without a human presence. The methodology employed is a descriptive empirical analysis, based on 2024 data provided by MatiPay Srl based in Mola di Bari (BA). Following an overview of key variables related to automated retail and business intelligence in the vending industry, the paper details the strategies adopted in the MatiPay Srl – Italy case study. The results of this analysis confirm a strong relationship between the improvement of advanced telemetry systems, new digital payment methods, and the innovative customer experience.